Anatomical Variants of Foramen Ovale and Foramen Spinosum. - Hema, Lattupalli; Kumari, Makani Tanuja; Rao, Madala Venkateswara (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Foramen ovale and spinosum are important foramina of the greater wingof the sphenoid. Normal variations in their shapes and sizes are quite common andwidely studied. Aim and Objectives: To conduct a morphometric study of foramen ovale andspinosum of the human sphenoid bone.Material and Methods: The present study was conducted over 100 dry humanskulls obtained from Anatomy department, Narayana Medical College, Nellore, andAndhra Pradesh. In this study presence of anatomic variations in shape of foramenovale and Spinosum was noted and length and width of foramen were measured.Various shapes of these two foramina were also noted and photographed.Comparison between right and left was done.Results: Mean length of foramen ovale was 5mm on the right side and 5.05mm onthe left side and mean width was 3.75mm on the right side and 2.65 mm on the leftside. There was no significantdifference between mean of the length and width of the right and left foramenovale. Foramen ovale was typically oval in 119 sides, almond in 12 sides, round in 55sides and slit like in 2.There was presence of fusion of foramen ovale and spinosumin one case. In case of foramen spinosum mean length on the right side is 2.25 mmand on the left side is 2.1respectively. Mean width on the right side is 3.55 mm andon the left side is 1.75 mm. foramen spinosum was round in 105 sides, oval in 23sides, pin hole in 32 sides and irregular in 40 sides.Conclusion: Anatomical variations in size and shape of foramen ovale could beexplained according to its development. Hence, considering the surgical anddiagnostic importance of foramen ovale and spinosum, this study would be added tothe literature for the future generations.